Foundations of play therapy - Schaefer, Charles E. (Wiley, 2011)
"Edited by Charles Schaefer, the "father of play therapy," this fully updated and revised Second Edition of Foundations of Play Therapy provides in-depth coverage of all the major models of play therapy from leading play therapists. Expert contributors provide detailed descriptions of all the major theoretical approaches to play therapy. Each chapter is fully revised and provides up-to-date discussions of the latest developments, applications, and empirical support for each theory. Play therapists and other mental health professionals will benefit from this landmark text"